PENGUASAAN KOSAKATA BAHASA INGGRIS MENGGUNAKAN PERMAINAN PICTIONARY - Azizah Hitari; Ramli R (LPPM Universitas Muhammadiyah Bulukumba, 2022)
This research aimed to develop students English vocabulary through the Pictionary game. This study was classroom action research in grade VII H 2nd group, SMPN 1 Tanjung Selor, consisting of 12 students. This study applied descriptive quantitative design and the data was collected using a written test. The collected data showed the students obtained the score minimum criteria of vocabulary development in the 1st circle and there was an improvement in the 2nd circle from the point 66.67 percent and 50 percent to 83.33 percent. The data analysis showed the implementation of Pictionary in English vocabulary learning could enhance students’ vocabulary and their learning outcome in grade VII H 2nd group, SMPN 1 Tanjung Selor.